La educación en valores y su incidencia en el comportamiento - Vásquez Santamaría, Verónica Bernarda (2022)
The research work that is put to consideration, seeks to analyze the problem of how to improve the behavior of sixth-year students of basic "A" of the Educational Unit September 19 of the Salcedo canton; having as objective the need to implement strategies of education in values with creative, valid and contextualized actions to contribute in the solution of the problem; For this, each of the stages was developed supported by a methodological design with a Quantitative approach, since it is analyzed whether education in the practice of values has an impact on the behavior of students; the type of research is descriptive, bibliographical, which has allowed determining as main results according to the situational diagnosis that; 37% of students consider that their parents never advise them to always act with respect, honesty and punctuality, in all acts of their lives; and also that 70% of boys and girls state that the teacher uses exhibitions for values education; However, once the proposal was applied in the classroom with the participation of the students and the support of each of the teachers, it has been possible to define the strategies that have had a positive impact in terms of education in values and its impact on the behavior of the students of the sixth grade "A" of Basic General Education of the Educational Unit September 19.